Exploring Artificial Intelligence as a Learning Companion in Distance Education: Student Motivation and Self-Regulated Learning in Islamic Higher Education - Faridur Rohman; Septi Gumiandari (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
This study affirms that the utilization of Artificial Intelligence (AI) as a learning partner in the Distance Learning (DL) system plays a significant role in shaping learning experiences, enhancing motivation, and strengthening self-regulated learning (SRL) among students of the Islamic Religious Education (IRE) Study Program at UIN Siber Syekh Nurjati Cirebon. This research employs a qualitative approach with a case study design, where data were collected through in-depth interviews, limited participant observation, and digital documentation, and then analyzed using NVivo software to produce a systematic thematic mapping. The findings show that students utilize AI as an adaptive and dialogic learning partner that supports understanding of learning materials, completion of assignments, and independent learning reflection. In addition, the use of AI has been proven to enhance learning motivation through the strengthening of autonomy, competence, and engagement, as well as encouraging SRL practices in planning, monitoring, and evaluating learning processes. However, this study also identifies challenges such as potential dependency, issues of information validity, and ethical concerns in the use of AI in learning. Thus, the integration of AI in DL needs to be implemented in a pedagogical, critical, and ethical manner in order to optimally contribute to improving the quality of student learning.